Pengaruh Kualitas Produk dan Iklan Terhadap Keputusan Pembelian Melalui Minat Beli Sepeda Motor Yamaha NMAX (Studi kasus pada Dealer Yamaha Bahana Pekalongan) - Bioma Zhahir; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2019)
Motorbikes are a means of transportation that is widely used by Indonesians. This makes competition in the Indonesian motorcycle market so competitive where many companies compete to win market share. Every company needs a high purchasing decision from consumers to be able to sell products according to the target. Product quality and advertising are factors that can influence purchasing decisions besides high consumer buying interest is also needed to create high purchasing decisions. The Yamaha Bahana Dealer Pekalongan also wants a high purchasing decision for its Yamaha NMAX products, but what happens is the purchase decision on Yamaha NMAX is low. This is because the quality of products and bad advertisements that affect consumers' buying interest is low so purchasing decisions are low. Based on the results of the analysis of the WarpPLS 5.0 calculation, it can be explained that the results of the direct influence test on this research model showed positive and significant effects. The test results of the indirect influence on the model indicate a positive but not significant effect on the product quality variable, as well as a positive and significant influence on the advertising variable. The effect of buying interest as a mediator in the model is partial mediation. Suggestions that can be conveyed from researchers are companies need to improve product quality and advertising to make Yamaha NMAX have more appeal so that buying interest and purchasing decisions can increase.